Processing of the Hepatitis E virus ORF1 nonstructural polyprotein - Karpe, Yogesh A. (Frontiers in Virology, 2024)
Hepatitis E viruses (HEV) Open Reading Frame 1 (ORF1) encodes a non-structural polyprotein. In most positive-sense RNA viruses found in animals, this non-structural polyprotein is cleaved by viral protease or host protease. However, the mechanism behind the processing of HEV polyprotein remains one of the most controversial questions in HEV biology. The role of putative HEV protease in processing is difficult to demonstrate. Recent studies have questioned the existence of HEV protease and suggested that pORF1 lacks protease activity. Conversely, studies also suggested the role of host proteases involved in the blood coagulation cascade, like thrombin, in processing the HEV pORF1 polyprotein. In summary, recent studies support the notion that pORF1 lacks protease activity and host proteases are responsible for processing pORF1. The present review compiles a thorough overview of contentious research on HEV's papain-like cysteine protease (PCP) and highlights recent advancements in the field. We aim to discuss the challenges and opportunities in the field to focus on further research.